Aphasia after stroke: natural history and associated deficits. - Wade, D T (1986)
Data relating to 976 patients registered as suffering an acute stroke has been analysed to determine the natural history of speech disturbance: these patients came from a community survey of 215,000 people over a 28 month period. Of the 545 patients assessed within 7 days of stroke, 24% were aphasic and 28% unassessable. At 3 weeks, when over 90% of survivors were tested, 20% of those tested had aphasia. At 6 months only 12% of survivors had significant aphasia, but 44% of patients and 57% of carers thought speech was abnormal. Of those aphasic within 7 days, 40% remained so at 6 months; 60% of those aphasic at 3 weeks remained so. There was a high correlation between early and late aphasia scores. Aphasia was associated with more severe disability (degree of limb weakness, loss of function, loss of IQ), and with a less good recovery of social activities, but did not cause any measurable increase in stress upon carers. In a Health District of 250,000 people, about 60 patients each year may be referred for speech therapy after an acute stroke.